Consumer perception and behaviour retention in gyms and health clubs - Gonçalves, Celina (2014)
The present study aims to find out to what extent the perception that the members have from gyms and health clubs (GHC) contributes to the retention and/or dropout, through specific variables of positioning. It tries to go beyond the exclusive study of quality, searching for a set of dimensions and indicators of positioning as important factors for retention and dropout.